1993
DOI: 10.1002/bit.260420415
|View full text |Cite
|
Sign up to set email alerts
|

A thermodynamically based correlation for maintenance gibbs energy requirements in aerobic and anaerobic chemotrophic growth

Abstract: A thermodynamic framework has been provided for the description of maintenance requirements of microorganisms. The central parameter is the biomass specific Gibbs energy consumption for maintenance, m(E) (kJ/C-mol biomass . h). A large set of data has been used including (i) a large range of different organisms (bacteria, yeasts, plant cells), (ii) mixed cultures, (iii) heterotrophic and autotrophic growth, (iv) growth under aerobic and anaerobic conditions, and (v) a large temperature range (5-75 degrees C). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
243
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(258 citation statements)
references
References 66 publications
13
243
2
Order By: Relevance
“…In our measurements, potential nitrification rates usually were one order of magnitude higher than the corresponding CO 2 fixation activities. This is in line with the 10:1 ratio of N oxidized per C incorporated reported for nitrifiers (Tijhuis et al, 1993;Middelburg, 2011) and suggests that CO 2 fixation in Baltic Sea hypoxic zones is coupled mainly to nitrification by AOA. In general, the rates of CO 2 dark fixation in hypoxic waters were notably lower than those in the upper sulfidic zone, a difference attributed to the activity in the latter of high numbers of chemoautotrophic denitrifiers of the Sulfurimonas sp.…”
Section: Discussionsupporting
confidence: 89%
“…In our measurements, potential nitrification rates usually were one order of magnitude higher than the corresponding CO 2 fixation activities. This is in line with the 10:1 ratio of N oxidized per C incorporated reported for nitrifiers (Tijhuis et al, 1993;Middelburg, 2011) and suggests that CO 2 fixation in Baltic Sea hypoxic zones is coupled mainly to nitrification by AOA. In general, the rates of CO 2 dark fixation in hypoxic waters were notably lower than those in the upper sulfidic zone, a difference attributed to the activity in the latter of high numbers of chemoautotrophic denitrifiers of the Sulfurimonas sp.…”
Section: Discussionsupporting
confidence: 89%
“…Because living cells have similar membranes and composition, it can be assumed that different cells require a similar amount of energy expenditure for maintenance. It has indeed been found that Gibbs energy needed for maintenance is very similar for a large range of microorganisms and only depends on absolute temperature (T) [11].…”
Section: Gibbs Energy For Maintenancementioning
confidence: 99%
“…A complete prediction of the growth stoichiometry thus requires a correlation for estimating the maintenance coefficient, which then enables one to compute Y X=S at low specific growth rates using the well-known Herbert-Pirt relation. Tijhuis et al [76] placed this argument on a thermodynamic foundation by observing that maintenance reactions will increase the Gibbs energy dissipation rate as shown by Eq. (40):…”
Section: Thermodynamic Analysis Of Maintenance Requirements and Thresmentioning
confidence: 99%
“…The following correlation for the maintenance Gibbs energy dissipation was developed by Tijhuis et al [76] based on an analysis of a large body of published data:…”
Section: Thermodynamic Analysis Of Maintenance Requirements and Thresmentioning
confidence: 99%